2018
DOI: 10.1039/c7qi00607a
|View full text |Cite
|
Sign up to set email alerts
|

Effective bandgap narrowing of Cu–In–Zn–S quantum dots for photocatalytic H2 production via cocatalyst-alleviated charge recombination

Abstract: Effective bandgap narrowing of Cu–In–Zn–S quantum dots is achieved with increased tolerance of Cu from the cocatalyst-alleviated charge recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 59 publications
0
41
0
1
Order By: Relevance
“…It has already been well demonstrated that noble metallic NPs play an important role in improving interfacial carriers transport efficiency by acting as electron traps or shifting the Fermi level of the semiconductor to a more negative level . For current work, tiny Au NPs prepared by in‐situ deposition are used to accelerate interfacial charge transfer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been well demonstrated that noble metallic NPs play an important role in improving interfacial carriers transport efficiency by acting as electron traps or shifting the Fermi level of the semiconductor to a more negative level . For current work, tiny Au NPs prepared by in‐situ deposition are used to accelerate interfacial charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the lack of highly active sites for redox reaction further reduces the PEC efficiency. Various noble metal‐based hybrid nanomaterials, including Au/Ag/Pd/Pt‐CuInS 2 and Pt‐CIZS have demonstrated the good PEC performance with help of the noble metals’ electron extraction ability and surface plasmon resonance‐mediated photocatalysis property . On the other hand, hole‐conducting layer such as CdS and poly (3‐octylthiophene) with strong wave function interfacial interaction also have been used as ideal holes transporters …”
Section: Introductionmentioning
confidence: 99%
“…在光伏器件中, 碳点通常直 接用作界面层, 但是与其他活性层或器件组件之间的接 口界面工程仍处于起步阶段, 这对于优化器件性能也是 非常重要的考量 [6,9,211,223,224] . [236][237][238][239][240][241][242][243][244] . 在 催化动力学上, 传统量子点兼具均相催化与非均相催化 的优点, 这些特性使传统量子点及其复合物在光催化应 用中具有独特的吸引力.…”
Section: 应用unclassified
“…[3][4][5] As a narrow bandgap n-type semiconductor (2.4 eV), CdS has been widely studied as a typical PEC photoanode, owing to its visible-light absorption, high charge mobility, appropriate band position for water redox reaction. [18][19][20][21][22] The sulfide/sulfite ions as hole scavengers are always necessary for stable operation. [10][11][12][13][14][15][16][17] However, many studies have revealed that the PEC activity of pure CdS is severely limited because of the highly photogenerated carrier recombination.…”
Section: Introductionmentioning
confidence: 99%